Thumb-Basal Joint Arthroplasty Outcomes and Metacarpal Subsidence: A Prospective Cohort Analysis of Trapeziectomy With Suture Button Suspensionplasty Versus Ligament Reconstruction With Tendon Interposition. (January 2023) - Shonuga, Owolabi; Nicholson, Kristen; Abboudi, Jack; Gallant, Gregory; Jones, Christopher; Kirkpatrick, William; Liss, Frederic; Takei, R. Robert; Wang, Mark; Ilyas, Asif M.
Background: Thumb carpometacarpal (CMC) joint arthroplasty is a common procedure in the surgical management of symptomatic thumb basal joint arthritis. Following trapeziectomy, a number of suspensionplasty techniques are often used, but limited comparative evidence exists between these techniques. The central aim of this study was to prospectively compare the outcomes of 2 suspensionplasty techniques following trapeziectomy: suture button (TightRope) versus ligament reconstruction and tendon interposition (LRTI). Methods: Prospective data were collected on 112 consecutive patients with Eaton stage III-IV thumb CMC arthritis who underwent open trapeziectomy and suspensionplasty. There were 53 LRTI and 59 TightRope suspensionplasty procedures. Outcomes were measured using the Quick Disabilities of the Arm, Shoulder, and Hand ( Quick DASH) questionnaire, Visual Analogue Scale (VAS) for pain, radiographic analysis, and lateral pinch strength. Patient demographic data and complications were also recorded. Results: Patients undergoing TightRope suspensionplasty had significantly higher trapeziometacarpal index and thus less subsidence than the LRTI group at 2 weeks (0.22 vs 0.17 [ P < . 0001]) and 3 months (0.17 vs 0.15 [ P < .05]) postoperatively. TightRope suspensionplasty also had a significantly lower Quick DASH score at 2 weeks (64.7 vs 74.6 [ P < .05]), 3 months (20.7 vs 32.5 [ P < .05]), and 1 year postoperatively (7.57 vs 21.5 [ P < .05]) compared with the LRTI group. However, there was no difference in VAS pain, lateral pinch strength, reoperation, or complications at any time point between groups. Conclusions: Thumb CMC joint arthroplasty performed with a TightRope suspensionplasty versus LRTI yielded short-term improved resistance to subsidence, long-term greater improvement in clinical outcome by Quick DASH, and no difference in pain or complication rates.